Open innovation among SMEs in Malaysia: The issue of trust - Mohd Nafi, Siti Noratisah; Yusoff, Rushami Zien; Thi, Lip Sam; Saad, Rohaizah (International Academic Research Journal, 2015)
The advancement of technology such as crowdsourcing, social media, and web applications has created a paradigm shift for innovation to move towards a more open platform such as open innovation.This paper examines the issues and challenges facing the implementation of open innovation among the small and medium-sized enterprises (SMEs) in Malaysia.It describes the importance of embracing this new paradigm in lined with the government targets to put forward productivity and innovation as the important pillar to drive the country's economic growth. There has been a substantial body of evidence to relate trust as an important component to business trends Although, there has been an exponentially rich study on trust across broad field and sciences, trust in the light of open innovation is still scarce.This paper aims to provide additional rationale and foundational support for the advancement of knowledge pertaining to trust and its relation to the open innovation via several dimensions namely the trust characteristics, innovation performance, organizational context, knowledge sharing and information technology (IT).